Study of Malondialdehyde Levels in sera, RBCs and Tissues homogenate of Iraqi Women With Breast Tumors (Baghdad Science Journal, 2009)
Breast tumors patients generally have more oxidative stress than normal females. This was clear from a highly significant elevation (P